RETRACTED: Mitigation of NaCl Stress by Arbuscular Mycorrhizal Fungi through the Modulation of Osmolytes, Antioxidants and Secondary Metabolites in Mustard (Brassica juncea L.) Plants - Sarwat, Maryam; Hashem, Abeer; Ahanger, Mohammad A.; Abd_Allah, Elsayed F.; Alqarawi, A. A.; Alyemeni, Mohammed N.; Ahmad, Parvaiz; Gucel, Salih (Frontiers in Plant Science, 2016)
Present work was carried out to investigate the possible role of arbuscular mycorrhizal fungi (AMF) in mitigating salinity-induced alterations in Brassica juncea L. Exposure to NaCl stress altered the morphological, physio-biochemical attributes, antioxidant activity, secondary metabolites and phytohormones in mustard seedlings. The growth and biomass yield, leaf water content (LWC) and total chlorophyll content were decreased with NaCl stress. However, AMF inoculated plants exhibited enhanced shoot and root length, elevated RWC, enhanced chlorophyll content and ultimately biomass yield. Lipid peroxidation and proline content were increased by 54.53% and 63.47% respectively with 200 mM NaCl concentration. Further increase in proline content and decrease in lipid peroxidation was observed in NaCl treated plants inoculated with AMF. The antioxidants, superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR) and reduced glutathione (GSH) increased by 48.35%, 54.86%, 43.85% and 44.44% respectively with 200 mM NaCl concentration. Further increase in these antioxidants has been observed in AMF colonized plants indicating the alleviating role of AMF to salinity stress through antioxidant modulation. The total phenol, flavonoids and phytohormones increase with NaCl treatment. However, NaCl treated plants colonized with AMF showed further increase in above parameters except ABA, which was reduced with NaCl+AMF treatment over the plants treated with NaCl alone. Our results demonstrated that NaCl caused negative effect on Brassica juncea seedlings; however, colonization with AMF enhances the NaCl tolerance by reforming the physio-biochemical attributes, activities of antioxidant enzymes, production of secondary metabolites and phytohormones.